The Use of Bioactive Compounds in Hyperglycemia- and Amyloid Fibrils-Induced Toxicity in Type 2 Diabetes and Alzheimer's Disease - Ancuta-Veronica Lupaescu; Monica Iavorschi; Mihai Covasa (MDPI AG, 2022)
It has become increasingly apparent that defective insulin signaling may increase the risk for developing Alzheimer's disease (AD), influence neurodegeneration through promotion of amyloid formation or by increasing inflammatory responses to intraneuronal β-amyloid. Recent work has demonstrated that hyperglycemia is linked to cognitive decline, with elevated levels of glucose causing oxidative stress in vulnerable tissues such as the brain. The ability of β-amyloid peptide to form β-sheet-rich aggregates and induce apoptosis has made amyloid fibrils a leading target for the development of novel pharmacotherapies used in managing and treatment of neuropathological conditions such as AD-related cognitive decline. Additionally, deposits of β-sheets folded amylin, a glucose homeostasis regulator, are also present in diabetic patients. Thus, therapeutic compounds capable of reducing intracellular protein aggregation in models of neurodegenerative disorders may prove useful in ameliorating type 2 diabetes mellitus symptoms. Furthermore, both diabetes and neurodegenerative conditions, such as AD, are characterized by chronic inflammatory responses accompanied by the presence of dysregulated inflammatory biomarkers. This review presents current evidence describing the role of various small bioactive molecules known to ameliorate amyloidosis and subsequent effects in prevention and development of diabetes and AD. It also highlights the potential efficacy of peptide-drug conjugates capable of targeting intracellular targets.